To be a 'Travesti’ is Questioning the (almost) Unquestionable: Gender as a Social Construction Process - Ramalho, Nélson (Gender, Sexuality and the Body: critical perspectives., 2014)
Gender is a social construction process based on strategies of power and domination. Normalization of gender expression through the prism of binary 'male' vs. 'female', not only hampers but masks the understanding of people who "violate" the social norms of gender, resulting in an oppressive process. Therefore, transgender people are systematically marginalized by discourses, institutions and policies that lead them to live of social vulnerability (Monro, 2005; Namaste, 2000). Direct observation in the context of sex work performed by ‘travesti’ people, especially in the area around ‘Conde de Redondo’, in Lisbon, over 16 months, has allowed us to understand that sex work, besides being a way of economic survival is also a form of construction of their social identity. It is through sex work that they learn that their sexual organs are sources of pleasure and desire. Unlike transsexuals, which often desire to remove their genitalia, seen often as a source of disgust, the 'travesti' may eventually challenge gender binarism, by questioning the traditional categories of 'male' and 'female', ‘man’ and ‘woman’. Despite living with a feminine appearance (breast enlargement, hips, thighs and buttocks), by body modifications through hormone ingestion and silicone application, travestis do not want, nor claim to 'be' women. This allows breaking the supposed ‘irreversible’ subjection of bodies to a supposed biologic order (Butler, 1999), thus exposing the complexity of gendered self-definition processes.